Bathing adaptations in the homes of older adults (BATH-OUT): protocol for a feasibility randomised controlled trial (RCT) - Whitehead, Phillip J.; James, Marilyn; Belshaw, Stuart; Dawson, Tony; Day, Miriam R.; Walker, Marion F. (BMJ Publishing Group, 2016)
Introduction The Care Act 2014 has placed a responsibility on local authorities in England to provide services that prevent deterioration and minimise the use of other health and social care services. Housing adaptations have been identified as 1 of the 10 most promising prevention services for older adults, with bathing adaptations being the most requested. However, many local authorities have lengthy waiting times which may increase costs, reduce effectiveness and reduce the preventive effect. There is no robust evidence of the effect of these adaptations on: health, well-being and functional ability.